2021
DOI: 10.1111/jan.14946
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between dyadic coping, intimate relationship and post‐traumatic growth in patients with breast cancer: A cross‐sectional study

Abstract: Aim To investigate the relationships and pathways between dyadic coping, intimate relationship and post‐traumatic growth (PTG) in Chinese patients with breast cancer. Design A cross‐sectional study. Methods Between November 2019 and November 2020, 133 patients with breast cancer who received therapy in tertiary grade‐A hospitals at Dalian, China completed questionnaires including demographic and clinical questionnaires, Locke–Wallace Marriage Adjustment Test, Chinese version of the Dyadic Coping Inventory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…The study of Lee, Cheng, and Chiou (2014) [41] explored the employment process of patients with SCI and recommended that patients with SCI should actively participate in related supportive social activities to understand their physiological limitations, prognosis, and undergo psychological and social adjustments through sharing with other patients or health professionals. Furthermore, the power of rebirth in this study is similar to cancer patients' post-traumatic growth, which opens new possibilities to their life [42]. In addition, Lee et al (2017) [16] indicated that patients must be trained on independent life functions as early as possible during the early stage of inpatient rehabilitation, and patient societies can be used or discharge preparation services can be strengthened.…”
Section: The Power Of Rebirthmentioning
confidence: 64%
“…The study of Lee, Cheng, and Chiou (2014) [41] explored the employment process of patients with SCI and recommended that patients with SCI should actively participate in related supportive social activities to understand their physiological limitations, prognosis, and undergo psychological and social adjustments through sharing with other patients or health professionals. Furthermore, the power of rebirth in this study is similar to cancer patients' post-traumatic growth, which opens new possibilities to their life [42]. In addition, Lee et al (2017) [16] indicated that patients must be trained on independent life functions as early as possible during the early stage of inpatient rehabilitation, and patient societies can be used or discharge preparation services can be strengthened.…”
Section: The Power Of Rebirthmentioning
confidence: 64%
“…To alleviate suffering, PTG is said to arise through self-disclosure and self-analysis due to a variety of coping strategies, distraction, talking to people, and changing intrusive thoughts into more positive ones. Shi et al ( 10 ) investigated 133 breast cancer patients in China. The results showed that binary coping and intimate relationship are the influencing factors of PTG, and strategies to improve the level of binary coping and avoid excessive intimate relationship between husband and wife are conducive to the occurrence of PTG in breast cancer patients.…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Post-traumatic growth (PTG), positive psychological changes after encountering traumatic events, has become an important indicator to measure the psychological recovery of cancer patients. Anxiety and depression were proven to affect the PTG of breast cancer patients ( Shi et al, 2021 ). Therefore, psychological interventions should be taken to reduce anxiety and depression, improve resilience, and promote PTG in breast cancer patients ( Li et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A visualization network of collaboration between countries and regions. Anxiety and depression were proven to affect the PTG of breast cancer patients (Shi et al, 2021). Therefore, psychological interventions should be taken to reduce anxiety and depression, improve resilience, and promote PTG in breast cancer patients (Li et al, 2020).…”
mentioning
confidence: 99%